Activity modulation of the Escherichia coli F1FO ATP synthase by a designed antimicrobial peptide via cardiolipin sequestering - Marcin Makowski; Víctor G. Almendro-Vedia; Marco M. Domingues; Octavio L. Franco; Iván López-Montero; Manuel N. Melo; Nuno C. Santos (iScience, 2023)
Summary: Most antimicrobial peptides (AMPs) exert their microbicidal activity through membrane permeabilization. The designed AMP EcDBS1R4 has a cryptic mechanism of action involving the membrane hyperpolarization of Escherichia coli, suggesting that EcDBS1R4 may hinder processes involved in membrane potential dissipation. We show that EcDBS1R4 can sequester cardiolipin, a phospholipid that interacts with several respiratory complexes of E. coli. Among these, F1FO ATP synthase uses membrane potential to fuel ATP synthesis. We found that EcDBS1R4 can modulate the activity of ATP synthase upon partition to membranes containing cardiolipin. Molecular dynamics simulations suggest that EcDBS1R4 alters the membrane environment of the transmembrane FO motor, impairing cardiolipin interactions with the cytoplasmic face of the peripheral stalk that binds the catalytic F1 domain to the FO domain. The proposed mechanism of action, targeting membrane protein function through lipid reorganization may open new venues of research on the mode of action and design of other AMPs.